Direct hydrogenation of amides to alcohols and amines under mild conditions - Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Shimon, Linda J. W.; Milstein, David (Journal of the American Chemical Society, 2010)
The selective, direct hydrogenation of amides to the corresponding alcohols and amines with cleavage of the C−N bond was discovered. The expected products of C−O cleavage are not formed (except as traces in the case of anilides). The reaction proceeds under mild pressure and neutral, homogeneous conditions using a dearomatized, bipyridyl-based PNN Ru(II) pincer complex as a catalyst. The postulated mechanism involves metal−ligand cooperation by aromatization−dearomatization of the heteroaromatic pincer core and does not involve hydrolytic cleavage of the amide. The simplicity, generality, and efficiency of this environmentally benign process make it attractive for the direct transformations of amides to alcohols and amines in good to excellent yields.

Efficient hydrogenation of organic carbonates, carbamates, and formates indicates alternative routes to methanol based on CO2 and CO - Balaraman, Ekambaram; Gunanathan, Chidambaram; Zhang, Jing; Shimon, Linda J. W.; Milstein, David (Nature Chemistry, 2011)
Catalytic hydrogenation of organic carbonates, carbamates and formates is of significant interest both conceptually and practically, because these compounds can be produced from CO2 and CO, and their mild hydrogenation can provide alternative, mild approaches to the indirect hydrogenation of CO2 and CO to methanol, an important fuel and synthetic building block. Here, we report for the first time catalytic hydrogenation of organic carbonates to alcohols, and carbamates to alcohols and amines. Unprecedented homogeneously catalysed hydrogenation of organic formates to methanol has also been accomplished. The reactions are efficiently catalysed by dearomatized PNN Ru(II) pincer complexes derived from pyridine- and bipyridine-based tridentate ligands. These atom-economical reactions proceed under neutral, homogeneous conditions, at mild temperatures and under mild hydrogen pressures, and can operate in the absence of solvent with no generation of waste, representing the ultimate ‘green’ reactions. A possible mechanism involves metal–ligand cooperation by aromatization–dearomatization of the heteroaromatic pincer core.

Electron-rich PNP- and PNN-type Ru(II) hydrido-borohydride complexes. synthesis, structure and catalytic activity towards dehydrogenation of alcohols and hydrogenation of esters - Zhang, Jing; Balaraman, Ekambaram; Leitus, Gregory; Milstein, David (Organometallics, 2011)
Electron-rich PNP- and PNN-type ruthenium(II) hydrido borohydride pincer complexes, [RuH(BH4)(tBu-PNP)] (tBu-PNP = (2,6-bis(di-tert-butylphosphinomethyl)pyridine) (5) and [RuH(BH4)(tBu-PNN)] (tBu-PNN = 2-di-tert-butylphosphinomethyl-6-diethylaminomethylpyridine) (6), were prepared from their corresponding N2-bridged dinuclear Ru(II) complexes [(tBu-PNP)RuCl2]2(μ-N2) (3) and [(tBu-PNN)RuCl2]2(μ-N2) (4), respectively. The X-ray structure of 5 reveals a BH4– anion η2 coordinated to ruthenium through two bridging hydrides. A variable-temperature 1H NMR study of 6 exhibits interesting fluxional behavior of the BH4– ligand. Similarly, the Ru(II) hydrido borohydride complex 9, in which the BH4– moiety is coordinated in a η1 bonding mode, was obtained by reaction of [RuCl2(PPh3)(iPr-PNP)] (iPr-PNP = 2,6-bis(diisopropylphosphinomethyl)pyridine) (8) with two equivalents of NaBH4 at room temperature. The hydrido borohydride pincer complexes 5, 6, and 9 catalyze the acceptorless dehydrogenative coupling of primary alcohols to esters and the dehydrogenation of secondary alcohols to the corresponding ketones, accompanied by evolution of hydrogen gas. The reactivity follows the order 6 > 9 > 5. With the hydrido borohydride complex 6 as catalyst, high yields (up to 98%) and high turnover numbers (TON ∼1000) were obtained in the dehydrogenation of primary alcohols under mild and neutral conditions. In addition, 6 effectively catalyzes the hydrogenation of nonactivated aromatic and aliphatic esters to the corresponding alcohols with TON ∼200 under a relatively mild pressure of dihydrogen and neutral and homogeneous conditions. Thus, an efficient homogeneous catalytic system for the dehydrogenation–hydrogenation reactions of alcohols is developed, which is relevant to the current interest in hydrogen storage.

New CNN-type ruthenium pincer NHC complexes. synthesis and catalytic activity. mild, efficient hydrogenation of esters - Fogler, Eran; Balaraman, Ekambaram; Ben-David, Yehoshoa; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2011)
New pincer ruthenium complexes (2–6) based on the new bipyridine-NHC ligand 1 were prepared and studied, resulting in an efficient catalytic hydrogenation of esters to the corresponding alcohols under mild conditions. Reaction of the ligand 1 with RuH(Cl)CO(PPh3)3, followed by reaction with one equivalent of the base KHMDS, gave the mixed phosphine-NHC complex 2, incorporating a C–H-activated bipyridine ligand. Complex 2 has an octahedral structure containing two phosphorus atoms trans to each other, a hydride trans to the NHC ligand, and CO trans to the C–H-activated carbon of the bipyridine ligand. Using the precursor complex Ru(p-cymene)Cl2(CO), reaction with 1 followed by treatment of the intermediate product with one equivalent of KHMDS resulted in formation of the dichloride pincer complexes 3a and 3b, which are in equilibrium, as indicated by variable-temperature 1H NMR. Complex 3a is an octahedral, neutral, and symmetric complex with the CO ligand positioned trans to the central pyridine group of the pincer ligand and the two chlorides trans to each other, as indicated by single-crystal X-ray diffraction. Complex 3b is cationic, with an outer-sphere chloride. Reaction of the NHC ligand 1 with LiHMDS at low temperature followed by addition of RuH(Cl)CO(PPh3)3 resulted in the mixed phosphine-NHC complex 4, which has an octahedral structure containing phosphorus trans to the hydride, a CO trans to the NHC ligand, and an outer-sphere chloride. Chloride substitution by BArF– gave the X-ray-characterized complex 5. Deprotonation of complex 4 with KHMDS resulted in formation of the dearomatized complex 6. The in situ prepared 6 (from complex 4 and an equivalent of base) is among the best catalysts known for the hydrogenation of nonactivated esters to the corresponding alcohols under mild conditions.

Synthesis of peptides and pyrazines from beta-aminoalcohols via extrusion of H2 catalyzed by ruthenium pincer complexes. ligand controlled selectivity - Gnanaprakasam, Boopathy; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Angewandte Chemie, 2011)
Bitte wählen: Die Wahl des Katalysators, eines Ru-Pinzettenkomplexes, bestimmt, ob Peptide oder Pyrazine aus β-Aminoalkoholen entstehen: Der PNN-Komplex 1 führt, je nach Substituent R (siehe Schema), zu linearem Polyalanin oder zu cyclischen Dipeptiden, der PNP-Komplex 2 katalysiert die Bildung von Pyrazinen. Die Reaktionen finden in homogener Lösung unter neutralen Bedingungen statt.

Unprecedented catalytic hydrogenation of urea derivatives to amines and methanol - Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Angewandte Chemie, 2011)
Indirekte CO2-Hydrierung: Eine Hydrierung von Harnstoffen zu Aminen und Methanol (siehe Bild) wird durch einen RuII-Pinzettenkomplex mit dreizähnigem bipyridinbasiertem PNN-Liganden katalysiert und verläuft unter milden, neutralen Bedingungen bei einem H2-Druck von 13.6 atm. Da sich Harnstoffderivate ausgehend von CO2 erhalten lassen, ermöglicht dieser Ansatz die indirekte Hydrierung von Kohlendioxid zu Methanol.

Efficient hydrogenation of biomass derived cyclic di-esters to 1,2-diols - Balaraman, Ekambaram; Fogler, Eran; Milstein, David (Chemical Communications, 2012)
The unprecedented homogeneous hydrogenation of cyclic di-esters, in particular biomass-derived glycolide and lactide, to the corresponding 1,2-diols is catalyzed by Ru(II) PNN (1) and Ru(II) CNN (2) pincer complexes under mild hydrogen pressure and (in the case of 1) neutral conditions. No racemization was observed when a chiral di-ester was used.

Novel ruthenium complexes and their uses in processes for formation and/or hydrogenation of esters, amides and derivatives thereof - Milstein, David; Balaraman, Ekambaram; Gunanathan, Chidambaram; Gnanaprakasam, Boopathy; Zhang, Jing (EP2629889A2, US9045381, US20130281664, WO2012052996A2, WO2012052996A3, 2012)
The present invention relates to novel Ruthenium complexes and related borohydride complexes, and their use for (1) hydrogenation of amides (including polyamides) to alcohols and amines; (2) preparing amides from alcohols with amines (including preparing polyamides (e.g., polypeptides) by reacting dialcohols and diamines or by polymerization of amino alcohols); (3) hydrogenation of esters to alcohols (including hydrogenation of cyclic esters (lactones), cyclic di-esters (di-lactones) or polyesters); (4) hydrogenation of organic carbonates (including polycarbonates) to alcohols and of carbamates (including polycarbamates) or urea derivatives to alcohols and amines; (5) dehydrogenative coupling of alcohols to esters; (6) hydrogenation of secondary alcohols to ketones; (7) amidation of esters (synthesis of amides from esters and amines); (8) acylation of alcohols using esters; (9) coupling of alcohols with water to form carboxylic acids; and (10) dehydrogenation of beta-amino alcohols to form pyrazines. The present invention further relates to novel uses of certain pyridine Ruthenium complexes.

Ruthenium pincer-catalyzed cross-dehydrogenative coupling of primary alcohols with secondary alcohols under neutral conditions - Srimani, Dipankar; Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Ben-David, Yehoshoa; Milstein, David (Advanced Synthesis & Catalysis, 2012)
Cross-dehydrogenative coupling of primary alcohols with secondary alcohols to obtain mixed esters with the liberation of molecular hydrogen is achieved in high yield and good selectivity under neutral conditions, using a bipyridyl-based PNN ruthenium(II) pincer catalyst.

Synthesis of polyamides from diols and diamines with liberation of H2 - Gnanaprakasam, Boopathy; Balaraman, Ekambaram; Gunanathan, Chidambaram; Milstein, David (Journal of Polymer Science Part A: Polymer Chemistry, 2012)
The amidation reaction based on catalytic coupling of alcohols with amines previously reported by us, using the pincer complexes 1 and 2 as catalysts, was applied to the generation of polyamides from nonactivated diols and diamines. A range of polymers was prepared, with Mn up to 26.9 kDa. Unlike the traditional syntheses of polyamides based on carboxylic acid derivatives, which require the use of toxic reagents and generate stoichiometric amounts of waste, this process generates only molecular hydrogen as byproduct. Both aromatic and aliphatic diols and diamines were used. Gel permeation chromatography measurements of the dimethylformamide-soluble polymers and thermal studies of the polyamides were performed. Matrix assisted laser desorption/ionization time-of-flight (MALDI-TOF) spectra are also reported. Thermogravimetric analyses studies indicate that the aromatic polyamides (with the exception of the pyridine-based polyamide) are more thermally stable than the aliphatic ones. This general, environmentally benign method for the synthesis of polyamides is homogeneously catalyzed under neutral conditions by dearomatized ruthenium-pincer complexes 1 and 2 and proceeds in 1,4-dioxane under an inert atmosphere. Conditions for polyamidation in the absence of solvent are also reported, using the pincer complex 2 as catalyst. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2012

Use of ruthenium complexes for formation and/or hydrogenation of amides and related carboxylic acid derivatives - Milstein, David; Gunanathan, Chidambaram; Ben-David, Yehoshoa; Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Zhang, Jing (US20120253042, US20160152663, 2012)
A process for preparing amides by reacting a primary amine and a primary alcohol in the presence of a Ruthenium complex to generate the amide and molecular hydrogen. Primary amines are directly acylated by equimolar amounts of alcohols to produce amides and molecular hydrogen (the only byproduct) in high yields and high turnover numbers. Also disclosed are processes for hydrogenation of amides to alcohols and amines; hydrogenation of organic carbonates to alcohols; hydrogenation of carbamates or urea derivatives to alcohols and amines; amidation of esters; acylation of alcohols using esters; coupling of alcohols with water and a base to form carboxylic acids; dehydrogenation of beta-amino alcohols to form pyrazines and cyclic dipeptides; and dehydrogenation of secondary alcohols to ketones. These reactions are catalyzed by a Ruthenium complex which is based on a dearomatized PNN-type ligand of formula A1 or precursors thereof of formulae A2 or A3.

Catalytic transformation of alcohols to carboxylic acid salts and H2 using water as the oxygen atom source - Balaraman, Ekambaram; Khaskin, Eugene; Leitus, Gregory; Milstein, David (Nature Chemistry, 2013)
The oxidation of alcohols to carboxylic acids is an important industrial reaction used in the synthesis of bulk and fine chemicals. Most current processes are performed by making use of either stoichiometric amounts of toxic oxidizing agents or the use of pressurized dioxygen. Here, we describe an alternative dehydrogenative pathway effected by water and base with the concomitant generation of hydrogen gas. A homogeneous ruthenium complex catalyses the transformation of primary alcohols to carboxylic acid salts at low catalyst loadings (0.2 mol%) in basic aqueous solution. A consequence of this finding could be a safer and cleaner process for the synthesis of carboxylic acids and their derivatives at both laboratory and industrial scales.

Formation of tertiary amides and H2 by dehydrogenative coupling of primary alcohols with secondary amines catalyzed by ruthenium bipyridine-based pincer complexes - Srimani, Dipankar; Balaraman, Ekambaram; Hu, Peng; Ben-David, Yehoshoa; Milstein, David (Advanced Synthesis & Catalysis, 2013)
Dehydrogenative coupling of primary alcohols with secondary amines to form tertiary amides and dihydrogen (H2) is efficiently catalyzed by bipyridyl-based ruthenium pincer complexes (0.2–1 mol%) under neutral conditions (in case of the dearomatized complexes), or with added catalytic amount of base. The reaction is sensitive to steric hindrance; in the case of amidation of bulky secondary amines a less sterically hindered complex is more efficient. Selective acylation of primary amines in the presence of secondary amines was also demonstrated.

PNN-Ru pincer complexes based on phosphinated 2,2’-dipyridinemethane- and 2,2’-oxobispyridine. metal-ligand cooperation in cyclometallation and catalysis - Barrios-Francisco, Rigoberto; Balaraman, Ekambaram; Diskin-Posner, Yael; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2013)
The synthesis of novel PNN ruthenium pincer complexes based on 2,2′-dipyridinemethane phosphine derivatives, as well as on 2,2′-oxobispyridine phosphine ligands, and their reactivity toward dearomatization and cyclometalation are described. The dearomatized compounds 7a,b undergo cyclometalation to yield complexes 8a,b. In order for cyclometalation to proceed, the coordination sphere around the Ru center has to rearrange, and this depends on the flexibility of the system, showing that the cyclometalation is qualitatively faster in the case of the dimethyl derivative 7a than in the case of the spyrocyclopentyl derivative 7b. The cyclometalation occurs diastereoselectively and leads to only one diastereomer of the cyclometalated compounds. In the case of the 2,2′-oxobispyridine complex 6c, the dearomatized complex was too unstable to be isolated; however it was possible to isolate and characterize a stable dicarbonyl-dearomatized ruthenium(II) complex, 9c, when the deprotonation was performed under a CO atmosphere. Dearomatization of 6a under CO also led to dicarbonyl-dearomatized ruthenium(II) complex 9a, which slowly rearranged into the dicarbonyl-aromatized ruthenium(0) complex 10a. These complexes were tested in catalytic alcohol–amine coupling, esterification of primary alcohols, and hydrogenation of secondary amides. Moderate activity was observed in hydrogenation of amides to alcohols and amines and low activity in the other transformations, owing mainly to the formation of stable cyclometalated compounds.

Stepwise metal-ligand cooperation via a reversible aromatization-deconjugation-sequence in ruthenium complexes with a tetradentate phenanthroline-based ligand - Langer, Robert; Fuchs, Ido; Vogt, Matthias; Balaraman, Ekambaram; Diskin-Posner, Yael; Shimon, Linda J. W.; Ben-David, Yehoshoa; Milstein, David (Chemistry - A European Journal, 2013)
The synthesis and reactivity of ruthenium complexes containing the tetradentate phenanthroline-based phosphine ligand 2,9-bis((di-tert-butylphosphino)methyl)-1,10-phenanthroline (PPhenP) is described. The hydrido chloro complex [RuHCl(PPhenP)] (2) undergoes facile dearomatization upon deprotonation of the benzylic position, to give [RuH(PPhenP-H)] (4). Addition of dihydrogen to 4 causes rearomatization of the phenanthroline moiety to trans-[Ru(H)2(PPhenP)] (5), followed by hydrogenation of an aromatic heterocycle in the ligand backbone, to give a new dearomatized and deconjugated complex [RuH(PPhenP*-H)] (6). These aromatization/deconjugation steps of the coordinated ligand were demonstrated to be reversible and operative in the dehydrogenation of primary alcohols without the need for a hydrogen acceptor. This aromatization/deconjugation sequence constitutes an unprecedented mode of a stepwise cooperation between the metal center and the coordinated ligand.

Synthesis, structures, and dearomatization by deprotonation of iron complexes featuring bipyridine-based PNN pincer ligands - Zell, Thomas; Langer, Robert; Iron, Mark A.; Konstantinovski, Leonid; Shimon, Linda J. W.; Diskin-Posner, Yael; Leitus, Gregory; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Inorganic Chemistry, 2013)
The synthesis and characterization of new iron pincer complexes bearing bipyridine-based PNN ligands is reported. Three phosphine-substituted pincer ligands, namely, the known tBu-PNN (6-((di-tert-butylphosphino)methyl)-2,2′-bipyridine) and the two new iPr-PNN (6-((di-iso-propylphosphino)methyl)-2,2′-bipyridine) and Ph-PNN (6-((diphenylphosphino)methyl)-2,2′-bipyridine) ligands were synthesized and studied in ligation reactions with iron(II) chloride and bromide. These reactions lead to the formation of two types of complexes: mono-chelated neutral complexes of the type [(R-PNN)Fe(X)2] and bis-chelated dicationic complexes of the type [(R-PNN)2Fe]2+. The complexes [(R-PNN)Fe(X)2] (1: R = tBu, X = Cl, 2: R = tBu, X = Br, 3: R = iPr, X = Cl, and 4: R = iPr, X = Br) are readily prepared from reactions of FeX2 with the free R-PNN ligand in a 1:1 ratio. Magnetic susceptibility measurements show that these complexes have a high-spin ground state (S = 2) at room temperature. Employing a 2-fold or higher excess of iPr-PNN, diamagnetic hexacoordinated dicationic complexes of the type [(iPr-PNN)2Fe](X)2 (5: X = Cl, and 6: X = Br) are formed. The reactions of Ph-PNN with FeX2 in a 1:1 ratio lead to similar complexes of the type [(Ph-PNN)2Fe](FeX4) (7: X = Cl, and 8: X = Br). Single crystal X-ray studies of 1, 2, 4, 6, and 8 do not indicate electron transfer from the FeII centers to the neutral bipyridine unit based on the determined bond lengths. Density functional theory (DFT) calculations were performed to compare the relative energies of the mono- and bis-chelated complexes. The doubly deprotonated complexes [(R-PNN*)2Fe] (9: R = iPr, and 10: R = Ph) were synthesized by reactions of the dicationic complexes 6 and 8 with KOtBu. The dearomatized nature of the central pyridine of the pincer ligand was established by X-ray diffraction analysis of single crystals of 10. Reactivity studies show that 9 and 10 have a slightly different behavior in protonation reactions.

Hydrogenation of polar bonds catalysed by ruthenium-pincer complexes - Balaraman, Ekambaram; Milstein, David (Ruthenium in Catalysis, 2014)
Catalytic hydrogenation of polar bonds using molecular hydrogen is an important, atom-economical synthetic reaction. Classical reduction methods of polar bond often require reactive metal-hydride reagents in stoichiometric amount and produce copious waste. Hydrogenation of carbonyl compounds in particular provides `green' approaches to synthetically important building blocks, such as alcohols and amines. We have designed and synthesized several ruthenium-based pincer catalysts for unprecedented hydrogenation reactions including: (1) amides to alcohols and amines, (2) biomass-derived di-esters to 1,2-diols and (3) CO2 and CO derivatives to methanol. These atom-economical reactions operate under neutral, homogeneous conditions, at mild temperatures, mild hydrogen pressures, and can operate in absence of solvent with no generation of waste. The postulated mechanisms involve metal-ligand cooperation (MLC) by aromatization-dearomatization of the heteroaromatic pincer core.
Keywords: Amides; Carbon dioxide; Esters; Hydrogen; Hydrogenation; Metal-ligand cooperation; Pincer complexes; ruthenium

Direct synthesis of secondary amines from alcohols and ammonia catalyzed by a ruthenium pincer complex - Balaraman, Ekambaram; Srimani, Dipankar; Diskin-Posner, Yael; Milstein, David (Catalysis Letters, 2015)
Efficient and selective direct synthesis of secondary amines from primary alcohols and ammonia with liberation of water has been achieved, with high turnover numbers and with no generation of waste. In case of benzylic alcohols, imines rather than amines are obtained. This atom economical, environmentally benign reaction is homogenously catalyzed by a well-defined bipyridine based Ru(II)-PNN pincer complex.
Keywords: Alcohol; Ammonia; Homogenous catalysis; Ru-pincer complex; Secondary amine